Creativity and the unconscious in the screenwriting classroom: A review of the literature. (1st June 2020) - Greenwood, Nell; Gibson, Robyn
Screenwriting pedagogy is a small but growing field of scholarly enquiry grappling with the challenges of a writing mode that demands a high level of creativity in order to render complex human experiences in a visual form bound by industrialized structures. Prominent screenwriters argue that engagement with unconscious thought is critical to achieving the high level of creativity required for this kind of writing. However, the unconscious remains a neglected area of enquiry in the fields of creativity and screenwriting research. This review of literature corrals existing research in both fields to synthesize insights for screenwriting and creative writing teachers on the engagement of unconscious thought as a means to enhance students' creativity.